"Making the best of what we have": The lived experiences of community psychiatric nurses, day centre managers and social workers supporting clients with dementia attending a generic day care service. (29th June 2017) - Laird, Elizabeth A.; McGurk, Phyllis; Reid, Bernie; Ryan, Assumpta
Abstract : Aim and objectives: This study explored the experiences and perspectives of community psychiatric nurses, day centre managers and social workers about supporting clients living with and without dementia attending a generic day care service. The purpose of the study was to elucidate approaches that enable clients living with dementia to access and derive benefit from the service. Background: In the light of international ageing demographics and strategy towards social inclusion, it is anticipated that demand for generic day care services for clients living with and without dementia will increase. Design and methods: A descriptive qualitative design utilised three focus groups for data collection. Community psychiatric nurses ( n  = 4), day centre mangers ( n  = 4) and social workers ( n  = 12) participated in the study. Data analysis informed a narrative description of the approaches that support adults living with dementia in day care. Findings: An exhaustive description is encapsulated in five key themes. These are " easing the transition to day care, " "proactively managing supervision and complexity of need, " "sustaining the person and family carer, " making the best of what we have" and "encountering a need for change, " The data conveyed a sensitivity to the life story and needs of clients with dementia. Whilst the data revealed deficits in the physical environment of the centres, there were indications of the generation of a positive social environment. Conclusions: A generic day care service that provides an integrated blend of care and treatment and social and recreational support to older adults, irrespective of whether they have or have not dementia, is realistic and manageable. The routine of day centre attendance may have value in sustaining clients with dementia and family care‐giving relationships. Implications for practice: Approaches to support the attendance of clients with dementia at day care include home visits, life story work, proactive supervision and careful planning of social groupings and recreational activities.